Solutions of a Class of Deviated-Advanced Nonlocal Problems for the Differential Inclusion x1(t)∈F(t,x(t)) - A. M. A. El-Sayed; E. M. Hamdallah; Kh. W. Elkadeky (Abstract and Applied Analysis)
We study the existence of solutions for deviated-advanced nonlocal and integral condition problems for the differential inclusion x1(t)∈F(t,x(t)).